Wacana Pragmatis Berbagai Agama Baru di Jepang - Sartini Sartini (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
The meaning of a religion and how to be religious in everysociety lead to different implication. Japanese define religiondifferently from Indonesian. The New Religions of the Japanesepropose new concepts of easy living, practical, optimism and say,worldly and master of their own destiny. To embrace, religionmeans to take advantage from them. Where as the Indonesianunderstand religion as private property with a lot of duties thatbelievers should follow sincerely.